The relationship of P53 gene mutation with clinicopathological characteristic in breast cancer - Amrank, Fitreena Anis (2016)
Background: P53 is a tumour suppresor gene. In breast cancer, p53 gene mutation were noted with frequency of about 30% (range 15 to 71%) and associated with poor prognosis. This study was perform determine p53 mutation association with clinicopathological characteristic in breast cancer and to assess the suitability of patients’ serum to detect p53 autoantibody. Methods: This study conducted in Hospital Seberang Jaya and Institut Perubatan dan Pergigian Termaju, Universiti Sains Malaysia. Six four breast cancer patients with available fresh breast cancer tissue that been kept under -80°C and with complete clinicopathological data involve in this study. These fresh breast tissues DNA extracted and 10sampels sent for DNA sequencing. The remaining 54samples proceeded with Polymerase Chains Reaction analysis based on the result from DNA sequencing. The serum of these patients was also taken for p53 autoantibody study using ELISA method. Results: The mean age of the patients in this study was 52.45±9.51 years. Most of the patients were Malay with 67.2% followed by Indian and Chinese with 17.2% and 15.6% respectively. About 51.6% of these patients undergone CT scan staging and 14.1% has distant metastases. p53 gene mutation prevalence showed rs1042522 only has 15.7% mutation. There was 54.7% Deletion A and 45.3% Wild Type A detected in rs59758982, 87.5% Deletion A and 12.5% Wild Type A in rs35069695 and 92.2 % recorded for Deletion GAA in rs376546152. There was no significant result between these mutation with breast cancer molecular classification and breast cancer aggressiveness except for rs59758982 shows significant result with p value 0.04 (p <0.05). In regards on for p53 serum auto antibodies, 20.3% of the patients noted to be positive but it has no significant association with p53 gene mutations.. Conclusion: In this study, tissue p53 genetic mutation has no significant association with clinicopathological characteristic of breast cancer and the use of serum p53 auto antibody as biomarkers is inconclusive.